Bowel perforation in Dego’s disease: a lethal surgical scenario - Vagholkar, Ketan; Iyengar, Madhavan; Vagholkar, Suvarna (International Surgery Journal, 2016)
Malignant atrophic papulosis or Dego’s disease is a type of cutaneous disease with involvement of the gastrointestinal and central nervous system. Involvement of the gastrointestinal system by way of perforation invariably leads to a fatal outcome. Awareness of this condition will help in providing a high index of suspicion while managing unexplained multiple intestinal perforations or while dealing with rapidly developing complications in perforative peritonitis.